ANALISIS PENILAIAN HARGA WAJAR SAHAM STUDI KASUS PADA PT MULTI BINTANG INDONESIA, TBK - SAYYIDIN NOOR, M (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: The purpose of this research is to calculate the intrinsic stock prices of the PT Multi Bintang Indonesia, Tbk. The analysis is using the dividend discounted model and the price earning ratio and then will be measured its accuracy level with root mean squared error. The result shows that stock prices of PT Multi Bintang Indonesia, Tbk using dividend discounted model is as overvalued stocks. The result also shows that stock prices of PT Multi Bintang Indonesia, Tbk using price earning ratio is as undervalued stocks. From accuracy test using root mean squared error, it implies that the method of price earning ratio is more accurate. The result suggested that to know intrinsic value of PT Multi Bintang Indonesia, Tbk is better using price earning ratio. Keywords: intrinsic stock prices, dividend discounted model, and price earning ratio.